Does central fatigue mediate the negative effect of prolonged mental exertion on subsequent endurance performance? - Pageaux, B.; Marcora, S.; Lepers, R. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Mental fatigue induced by prolonged and demanding cognitive tasks is well known to impair cognitive performance. A recent study (1) demonstrated that mental fatigue also reduces time to exhaustion during high-intensity cycling exercise. This negative effect of mental fatigue on endurance performance may be mediated by its effects on neuromuscular function. The first hypothesis is that prolonged mental exertion induces significant central fatigue defined as reduced ability of the central nervous system to fully recruit the active muscles during a maximal effort (2). The second hypothesis is that mental fatigue exacerbates the central fatigue induced by prolonged submaximal exercise and consequently reduces endurance performance. The aim of this study was to test these two hypotheses by assessing neuromuscular function in two different conditions: A) before and after a prolonged and demanding cognitive task known to induce mental fatigue (AX-CPT task); B) before and after an easy cognitive task (watching a movie). Both cognitive tasks were followed by a submaximal knee extensors contraction performed until exhaustion, and a third assessment of peripheral and central fatigue. Rating of perceived exertion was measured during the time to exhaustion test. Results are presented as means ± SD, and analysed by paired t-tests or two-way repeated-measure ANOVAs. Time to exhaustion was 13% shorter in the mental fatigue condition (230 ± 72 s) compared to control condition (266 ± 82 s) (P<0.01). However, prolonged and demanding cognitive activity did not have any significant effect on maximal voluntary contraction (MVC), voluntary activation level (VAL) and peripheral parameters of neuromuscular function. Neuromuscular alterations induced by the endurance exercise were in accordance with the literature (3). However, a similar decrease in MVC (mental fatigue 26.7 ± 17.9 %, control 27.6 ± 10.3 %) and VAL (mental fatigue - 10.6 ± 13.5 %, control - 11.2 ± 16.4 %) occurred in both conditions (Fig 1). Evolution of EMG indexes of vastus lateralis and rectus femoris muscles activation was similar to VAL values. Mentally fatigued subjects rated perception of effort higher during the time to exhaustion test compared to the control condition (P<0.05) (Fig 2). In conclusion, these findings provide the first experimental evidence that mental fatigue does not induce or exacerbate central or peripheral fatigue. Therefore, the reduction in endurance performance observed in mentally fatigued subjects cannot be mediated by a reduction in neuromuscular function. As suggested by the psychobiological model of endurance performance (4), the most likely mechanism for the negative effect of mental fatigue on time to exhaustion is the increase in perception of effort experienced by mentally fatigued subjects.